Relationship of Extrinsic Risk Factors to Lower Extremity Injury in Collegiate Ballet Dancers - Huang, Pi-Yin; Lin, Chia-Wei; Jankaew, Amornthep; Lin, Cheng-Feng (Frontiers in Bioengineering and Biotechnology, 2022)
Ballet dancers are thought to be at higher risk of lower extremity injury. This study was to describe the self-reported incidence, location, and factors associated lower extremity injury in collegiate ballet dancers. Two hundred and forty nine female ballet dancers responded to a questionnaire that addressed their injury event/location, dance behavior over the past 2 years; and overall dance history. Behaviors assessed included: Types and number of shoes worn (pointé shoes/ballet slippers), wear time, training time (session frequency and duration); use of warm-up/cool-down; and use of a strengthening program and lower extremity accessory. Overall dance history included age of onset of training, total years of experience and number of dance styles. Backward multivariable logistic regression analysis was used to determine the extent to which variables measured were associated with injury. Ankle injury was the most prevalent injury. Years of wearing pointé shoes (adjusted Odds ratio = 1.21, P = 0.01) and days/week in pointé shoes (adjusted Odds ratio =1.26, P = 0.04) were associated with increased risk of injury; while additional strengthening (adjusted Odds ratio = 0.39, P = 0.02) and use of lower extremity accessories during classes/rehearsals (adjusted Odds ratio = 0.64, P = 0.01) were protective associations. These findings suggested that use of pointé shoes, lower extremity accessories, and additional exercise should specifically be recorded during evaluation of injured ballet dancers; and considered as potential factors to modify during rehabilitation.